2019
DOI: 10.1186/s12868-019-0498-4
|View full text |Cite
|
Sign up to set email alerts
|

Affective and cognitive behavior is not altered by chronic constriction injury in B7-H1 deficient and wildtype mice

Abstract: Background Chronic neuropathic pain is often associated with anxiety, depressive symptoms, and cognitive impairment with relevant impact on patients` health related quality of life. To investigate the influence of a pro-inflammatory phenotype on affective and cognitive behavior under neuropathic pain conditions, we assessed mice deficient of the B7 homolog 1 (B7-H1), a major inhibitor of inflammatory response. Results Adult B7-H1 ko mice and wildtype littermates (WT) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, Tyrtyshnaia's study found that short-term memory in CCI mice was signi cantly impaired as early as 14 days after surgery (Tyrtyshnaia et al 2017). Other study indicated that mice after CCI did not develop cognitive impairment examined by the novel object recognition test (Karl et al 2019). These discrepancies could be attributed to different behavioral protocols (the training protocol of Y-Maze used in Tyrtyshnaia's study is different from ours) or experiment conditions, for example different types of suture make the difference of the tension of the ligatures (Maves et al 1993), as there is a great inter-and intra-individual experimenter variability.…”
Section: Discussionmentioning
confidence: 98%
“…However, Tyrtyshnaia's study found that short-term memory in CCI mice was signi cantly impaired as early as 14 days after surgery (Tyrtyshnaia et al 2017). Other study indicated that mice after CCI did not develop cognitive impairment examined by the novel object recognition test (Karl et al 2019). These discrepancies could be attributed to different behavioral protocols (the training protocol of Y-Maze used in Tyrtyshnaia's study is different from ours) or experiment conditions, for example different types of suture make the difference of the tension of the ligatures (Maves et al 1993), as there is a great inter-and intra-individual experimenter variability.…”
Section: Discussionmentioning
confidence: 98%
“…5B ). Additionally, this parameter is also used in other MWM studies [ 95 , 156 , 167 , 168 ], highlighting its relevance for probe trial analysis.…”
Section: Different Protocols and Analysis Methods For The Morris Wate...mentioning
confidence: 99%
“…Due to the involvement of B cells, NK cells, DCs, microglia/macrophages in MS pathology, the expression of PD-1/PD-L1 on these cells may also engage in MS development. Specifically, PD-1/PD-L1 not only limits autoimmunity in the CNS, but also exerts influences on acute and chronic pain, affective and cognitive behaviors [199,200]. Therefore, additional physiological functions of PD-1/PD-L1 in the CNS may provide new insights in MS pathogenesis.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%